BINARY LOGISTIC MODEL APPROACH TO THE DECISION OF MSME ACTORS IN CHOOSING SYARIAH BANKING FINANCING - Amalia; Abd. Rahim; Sri Astuty; Diah Retno Dwi Hastuti; Regina (Jurnal Syarikah : Jurnal Ekonomi Islam, 2025)
The development of the Syariah banking industry in Indonesia has experienced significant growth, marked by the increasing network of Syariah banking offices that expand the accessibility of financial services for the community, including MSME players. BTPN Syariah, as one of the Syariah financial institutions that focuses on empowering MSMEs, has channeled Syariah financing with an increasing trend during the period 2020 to 2024. This study aims to analyze the factors that influence MSME decisions in choosing Syariah banking financing in Somba Opu District. This research includes quantitative research with a survey approach. The sample in this study was taken by accidental sampling technique. The total sample was 98 respondents. Data collection used in the study using a questionnaire. The analysis method used is Binary Logistic. The results showed that the level of education has a significant negative effect and the length of business has a significant positive effect on the decision of MSMEs to choose Syariah financing, while the level of income has no significant effect.